An Introduction to Global Spectral Modeling. - Krishnamurti, T. N. (Oxford University Press, 1998)
This is an introductory text on numerical weather prediction (numerically modelling the general circulation of the atmosphere), utilizing the spectral transform method. It covers infinite difference methods and time-differencing schemes; the theoretical development of the spectral transform method; physical processes; data analyses and more.